Вычислить неопределённый интеграл(с подробным решением)

Эллада20029 Эллада20029    2   19.01.2020 03:52    0

Ответы
SashaPolishuk SashaPolishuk  11.10.2020 01:43

\frac{1}{6}*\sqrt{(1-\frac{2}{x^{2}} )^{3}} +C

Пошаговое объяснение:

\int\limits {\frac{\sqrt{x^{2}-2 } }{x^{4} } } \, dx =\int\limits {\sqrt{\frac{x^{2}-2 }{x^{2} } } *x^{-3} } \, dx =\int\limits {\sqrt{1-\frac{2}{x^{2} } } * (-\frac{1}{2} )} \, d(x^{-2} ) =\\\\=\int\limits {\sqrt{1-2*x^{-2}} } * \frac{1}{4} } \, d(-2*x^{-2} ) =\\\\=\frac{1}{4}*\int\limits {(1-2*x^{-2})^{\frac{1}{2} } } } \, d(1-2*x^{-2} ) =\\

=\frac{1}{4}*\frac{(1-2*x^{-2})^{\frac{1}{2} +1} }{\frac{1}{2} +1} +C =\frac{1}{4}*\frac{(1-2*x^{-2})^{\frac{3}{2} } }{\frac{3}{2}} +C =\\\\=\frac{1}{4}*\frac{2}{3}*(1-2*x^{-2})^{\frac{3}{2} }+C=\frac{1}{6}*\sqrt{(1-\frac{2}{x^{2}} )^{3}} +C

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика

Популярные вопросы